Eigennamen en “Makùmbù” Van “Mvìdi Mukùlù” bij de Balubà-Kàsaayì - Horvath, Ellen (Afrika Focus, 1998)
This article attempts to analyze the proper names and "makùmbù " (or praise-names) bestowed upon the supreme being or God by the Balubà-Kàsaayï. This is done in order to have a better insight in their conceptions of God. The Balubà-Kàsaayï give several names to God, such as Mvïdi Mukùlù, Maweeja, Mulopd and Nzambi. These names are used in the makùmbù, oral formulae consisting of one or two sentences. In general they are used to praise people, spirits, animals, plants, places and even things, emphasizing their qualities. The makùmbù are used as a complementary element to or a substitution of the proper name. The makùmbù addressed to God refer to his greatness, eternity, freedom, etcetera. KEY WORDS: Congo, Balubà-Kàsaayï, God, proper names, makùmbù.